2020
DOI: 10.1017/s0967199420000155
|View full text |Cite
|
Sign up to set email alerts
|

Does cigarette smoking really have a clinical effect on folliculogenesis and oocyte maturation?

Abstract: Summary Infertility is the most common issue in the field of reproductive medicine. Many factors affect fertility status, including life-style choices such as cigarette smoking or alcohol use. The aim of this study was to investigate the effects of cigarette smoking on oocyte quality as well the quantity in young fertile women. In total, 56 young fertile women who were undergoing oocyte donation programmes were included in this study. The effects of cigarette smoking on antral follicle count, number of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Remarkably, the sperm counts in the rats handled by the non-nicotine liquid was 32.3 ± 3.0 million/mL or 38.4 ± 0.9 million/mL, accordingly, compared to the other subgroup handled with nicotine. Assessing the vitality of sperm for treated rats yielded similar findings, with 27.0% ± 4.6% to 42.8% ± 5.1% of viable sperm [39]. A morphological analysis revealed a statistically significant rise in the proportion of aberrant sperm, particularly in the rats subjected to the nicotinefree liquid compared to the nicotine-containing liquid compared the untreated group, at 43.0% ± 1.0% vs. 30.2% ± 1.8% vs. 24.0% ± 0.9%.…”
Section: Issn: 2583-4053mentioning
confidence: 58%
See 1 more Smart Citation
“…Remarkably, the sperm counts in the rats handled by the non-nicotine liquid was 32.3 ± 3.0 million/mL or 38.4 ± 0.9 million/mL, accordingly, compared to the other subgroup handled with nicotine. Assessing the vitality of sperm for treated rats yielded similar findings, with 27.0% ± 4.6% to 42.8% ± 5.1% of viable sperm [39]. A morphological analysis revealed a statistically significant rise in the proportion of aberrant sperm, particularly in the rats subjected to the nicotinefree liquid compared to the nicotine-containing liquid compared the untreated group, at 43.0% ± 1.0% vs. 30.2% ± 1.8% vs. 24.0% ± 0.9%.…”
Section: Issn: 2583-4053mentioning
confidence: 58%
“…The World Health Organisation (WHO) reports that 30% of males aged 15 or older smoke [6][7]. About 46% of smokers are men who are of age to reproduce (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). The real number of smokers climbed from 721 million in 1980 to 967 million for 2012, despite the fact that the proportion of adult smokers, based By the World Health Organisation, infertile affects 8% for spouses globally including 10% -15% of spouses throughout developed countries, with male factor contributing to 30% -35% of instances.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, differences in study populations can't be excluded. Previous reports suggested that some diseases, e.g., endometriosis [98-101], and even some social habits, e.g., smoking [102], may have detrimental effects on oocyte morphology and quality. In our studies, there were no signi cant differences between the two groups in any patient's characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that cigarette smoking did not affect the follicles count and the number of oocytes retrieved. However, a significant difference was detected in the morphological assessment of oocyte including cytoplasmic anomalies [126].…”
Section: Female Smoking and Assisted Reproductive Treatment (Art)mentioning
confidence: 95%